Oil Price Volatility And Macroeconomics, Does It Affect The Performance Of Islamic Stocks In The Jakarta Islamic Index? - Baroroh, Hilmy; Azka, Mohammad Shadam Taqiyyuddin; Afifah, Sabrina Nur (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to determine the effect of world crude oil prices and macroeconomics on the performance of Islamic stocks in the Jakarta Islamic Index (JII).Method - The research approach uses quantitative with the Autoregressive Distributed Lag (ARDL) method to analyze the short-term and long-term influence. The research sample was taken from as many as 29 companies included in the JII Index with the observation period from 2016-2022.Result - The results of this study show that the relationship between crude oil prices and Islamic stock performance has a significant negative effect. The rupiah exchange rate has a significant negative effect on the performance of Islamic stocks. Central bank interest rates, in this case using the BI Rate, have a significant positive effect on the performance of Islamic stocks. Inflation has a significant positive effect on the performance of Islamic stocks. Implication - This study uses Islamic stock performance data from each company listed in the Jakarta Islamic Index and macroeconomic data obtained based on bank indonesia reports and crude oil prices derived from WTI crude oil prices. Originality- This study looks at the short-term and long-term effects of crude oil prices and macroeconomics on the performance of Islamic stocks in the JII. The ARDL method is used to provide accurate results.